The commodity structure of export and import of Ukraine during the war – a legacy - Kalenska, V. P. (Global Prosperity, 2023)
In addition to the many challenges facing the Ukrainian economy, namely, COVID-19, rising prices for gas and other energy sources, the war has been added. Russia's invasion of Ukraine on February 24, 2022 resulted in the cessation of imports of most product categories, as many businesses suffered physical losses, infrastructure was damaged, and foreign partners suspended cooperation with Ukraine due to increased risks. In this situation, Ukrainian business had to survive and do everything possible to save jobs, the enterprises/industries themselves, and the country itself. The work analyzes the dynamics of foreign trade for 2018-2022. The main exporting and importing countries of Ukraine during the war are identified. The commodity structure of Ukraine's exports and imports in 2022 is characterized. The model for the development of the competitiveness of Ukraine's economy during and after the war will be successful when it is built on advantages determined by national determinants of competitiveness and adapted to the influence of the external environment. First of all, in order to restore Ukrainian exports and imports, it is necessary to end hostilities on the territory of Ukraine.